Sodium-Glucose Co-Transporter 2 Inhibitors May Change the Development of Urinary Tract and Hematological Malignancies as Compared With Dipeptidyl Peptidase-4 Inhibitors: Data of the Post-Hoc Analysis of a Nationwide Study - Rokszin, György; Kiss, Zoltán; Sütő, Gábor; Kempler, Péter; Jermendy, György; Fábián, Ibolya; Szekanecz, Zoltán; Poór, Gyula; Wittmann, István; Molnár, Gergő Attila (Frontiers in Oncology, 2021)
Background In diabetes mellitus, during the last years, cancer became of equivalent importance as a cardiovascular disease in terms of mortality. In an earlier study, we have analyzed data of the National Health Insurance Fund (NHIF) of Hungary with regards all patients treated with sodium-glucose co-transporter 2 (SGLT2) inhibitors (SGLT2is) vs. those treated with dipeptidyl peptidase-4 (DPP-4) inhibitors (DPP-4is) in a given timeframe. In propensity score-matched groups of SGLT2i- vs. DPP-4i-treated patients, we found a lower incidence of cancer in general. In this post-hoc analysis, we aimed to obtain data on the incidence of site-specific cancer. Patients and Methods All patients starting an SGLT2i or a DPP-4i between 2014 and 2017 in Hungary were included; the two groups (SGLT2i vs. DPP-4i) were matched for 54 clinical and demographical parameters. The follow-up period was 639 vs. 696 days, respectively. Patients with a letter “C” International Classification of Diseases, 10th Revision (ICD-10) code have been chosen, and those with a known malignancy within a year before the onset of the study have been excluded from the analysis. Results We found a lower risk of urinary tract [HR 0.50 (95% CI: 0.32–0.79) p = 0.0027] and hematological malignancies [HR 0.50 (95% CI: 0.28–0.88) p = 0.0174] in patients treated with SGLT2i vs. those on DPP-4i. Risk of other types of cancer (including lung and larynx, lower gastrointestinal (GI) tract, rectum, pancreas, non-melanoma skin cancers, breast, or prostate) did not differ significantly between the two groups. When plotting absolute risk difference against follow-up time, an early divergence of curves was found in case of prostate, urinary tract, and hematological malignancies, whereas late divergence can be seen in case of cancers of the lung and larynx, the lower GI tract, and the breast. Conclusions Urinary tract and hematological malignancies were less frequent in patients treated with SGLT2i vs. DPP-4i. An early vs. late divergence could be observed for different cancer types, which deserves further studies.